Characterization of Epilithic Microbial Communities Associated with Mayan Stone Monuments in Yucatan, Mexico - Ortega-Morales, O; Hernandez-Duque, G; Borges-Gomez, L; Guezennec, J (Geomicrobiology journal, 1999)
The microbial epilithic communities associated with Uxmal Mayan stone monuments (Yucatan, Mexico) were preliminarily characterized by chemical and biochemical methods. The organic matter, organic carbon, and nitrogen content were within the respective ranges reported for other stone buildings, indicating that oligotrophic conditions prevailed at Uxmal's buildings. Quantitative differences in both total and phototrophic biomass were observed between stone and mortar (stucco) substrata, between indoor and outdoor locations, and between seasons. Microbial biomass and organic matter content were greater on indoor surfaces associated with more suitable microenvironmental conditions (availability of water and protection from direct sunlight) for microbial growth. Cyanobacterial photosynthesis, microbial debris, and bird droppings are the most probable sources of organic carbon and organic nitrogen in Uxmal's stone buildings. The epilithic communities appear to be dominated by phototrophs (mainly cyanobacteria) populations and associated bacteria. The latter are probably trophically dependent on the release of organic matter by photosynthetic production. These microbial biofilms and their activity may be responsible, in part, for the degradation of these stone monuments.